Economic aspects of the Kr-Xe mixture production and enrichment - Бондаренко, Виталий Леонидович; Корж, Елизавета Григорьевна; Дьяченко, Татьяна Викторовна; Дьяченко, Ольга Валерьевна (Technology audit and production reserves, 2014)
The present work deals with studying the structure of costs for extracting krypton-xenon mixture, produced as a byproduct of separation of air and krypton-xenon concentrate after its enrichment in individual plants. Reducing the costs of manufacturing products allows to reduce their prime cost and therefore increase the profits of the enterprise. As the object of investigation, oxygen production of large metallurgical enterprise was considered. Comparison of the known methods for calculating the prime cost of air separation byproducts was conducted, the main sources of costs for producing krypton-xenon mixture was analyzed. Components of the prime cost of krypton-xenon concentrate, produced during its enrichment in “Chrome”-type plants were investigated. Calculations have shown that energy costs (70-80 % of total costs) make the main contribution to the prime cost of the krypton-xenon mixture, produced in air separation plants. General production equipment maintenance costs and expenses constitute 20-30%. Contribution of wages fund is from 2 to 5%, depending on the wage level, adopted in the metallurgical industry. In enriching the krypton-xenon primary mixture in “Chrome”-type plants, energy costs (60% of all expenses) are also determining. Among them, 7% accounts for the production krypton-xenon concentrate compression. Wages are about 17% of total costs. Share of original Kr-Xe mixture in the prime cost of concentrate is about 9%. Studies have allowed to define “critical” items of expenses, changing which most affects the prime cost of intermediate mixtures and, finally, krypton and high-purity xenon sales profit margin.